THE EFFECT OF ORGANIZATIONAL COMMUNICATION TOWARD EMPLOYEES PERFORMANCE - Jazuli Dian Kurniawan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
The purpose of this research is to analyze the influence of organizational communicationtoward employee performance. There are three independent variables included in the upwardcommunication, downward communication and horizontal/lateral communication. The threeindependent variables were investigate to see the impact on employee performance. Thisresearch conducted at Ngadiredjo Sugar Company with 137 respondents.The sampling technique used is random sampling and the research instruments weretested using the validity test, reliability test, and classical assumption test. The hypotheses usedpartial (t-test). Result of the data analysis from multiple regression showed that the threeindependent variables give significant effect on the employee performance. The results of thisresearch can be applied for the organization and interested parties to maintain and maximize theorganizational communication to get a positive effect on employee performance.Keywords: Upward Communication, Downward Communication, Horizontal/LateralCommunication, Employee Performance